Explanation on How to Interpret Properly the Bioefficacy of Methionine Hydroxy Analog-Free Acid Relative to Dl-Methionine Estimated by Regression Models in Laying Hens - Bateman, A.; Liu, Z.; Bryant, M.M.; Wu, G.; Sr., D.A. Roland (International Journal of Poultry Science, 2005)
Two studies were conducted to compare bioefficacy of liquid DL-methionine hydroxy analogue-free acid (MHA-FA) and DL-methionine (DL-Met). Biological efficacy was determined for egg production, feed consumption, egg mass, and egg weight using linear and nonlinear regression models. In Experiment 1, five levels of DL-Met (0.023, 0.045, 0.068, 0.090 and 0.113%) and MHA-FA (0.026, 0.051, 0.077, 0.102 and 0.128%) were added on an equimolar basis to a basal diet containing 14.97% protein and 0.27% Met. This trial used 1,760 first cycle, Phase II Hy-Line W-36 hens. There was no response above the basal diet in any of the criteria measured, so regression analysis was not performed. In Experiment 2, five levels of DL-Met (0.012, 0.024, 0.036, 0.048 and 0.060%) and MHA-FA (0.014, 0.027, 0.041, 0.054 and 0.068%) were added on an equimolar basis to the basal diet used in Experiment 1. This trial used 1,760 second cycle, Phase I Hy-Line W-36 hens. The average bioefficacy of MHA-FA related to DL-Met was 82.45% on a weight basis (or 93.70% on a molar basis) based on egg production, was 89.23% on a weight basis (or 101.40% on a molar basis) based on egg mass, and was 106.29% on a weight basis (or 120.79% on a molar basis) based on egg weight, more research is needed to improve accuracy of bioefficacy values.